The Current Brazilian Forestry Code and its Implications for the Prevention of Natural Disasters - Coutinho, Marcos Pellegrini; de Deus Medeiros, João; Soriano, Érico; de Resende Londe, Luciana; Vaitsman Leal, Paulo Jorgel; Midori Saito, Silvia (Sustainability in Debate, 2013)
We have analyzed the changes in the Brazilian law 12.651/2012 in comparison with the former one (Forest Code, 1965) and presented the implications for civil defense institutions and society. We have used scientific articles and passages from the law and other regulation documents as a starting point to discuss the importance of areas of permanent preservation (APPs) to reduce natural disasters and to promote an appropriate process of urban occupation. When discussing disasters prevention, it is mandatory to obey the APPs regulation, both in irregular settlements and in areas used for urban occupation. The regulation of these areas must consider the ecosystem services provided by the municipalities’ green areas, further than reducing mass movimens and floods. This regulation must provide healthy coexistence, leisure, education and better quality of life for its population.